Potential for harvesting electrical energy from swing and revolving door use. Issue 1 (1st January 2018) - Partridge, J.S.; Bucknall, R.W.G.
Abstract: This paper considers the energy generation potential from swing and revolving door use. This involved modelling the mechanical work available from the single use of swing and revolving doors through consideration of the doors motion using Matlab. The equations of motion of swing and revolving doors were presented and several sources of harvestable mechanical energy were explored. The impact on the motion and energy generation potential of several parameters such as the door mass, door width and damping of the generator were considered. It was found that door use has potential for electrical energy generation. For a swing door somewhere in the region of 10 J could be expected from a single action. A revolving door was found to offer significantly greater potential were a user to rotate the door by 180°, this would be in the region of 40 J. This equates to an upper limit for the total energy generation potential over a 1 min period of 138 J for a swing door and 331 J for a revolving door. It was concluded that potential for the generation of electrical energy exists from door use. It was determined that this will be dependent on the generation method chosen and the type of door used, where revolving doors offer significantly more potential than swing doors for both a single occasion door use and over a 1 min period.